Internalisasi Nilai-Nilai Budaya Religius Melalui Kegiatan Keagamaan di MTs N 3 Ponorogo - Wahidah, Septia Nur; Heriyudanta, Muhammad (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2021)
Abstract The provision of general and religious education materials must be in harmony with each other, an imbalance in the provision of religious material will result in the loss of internal values in students. For this reason, planting and cultivating religious material at various levels of education is a must in the midst of rapid advances in science and technology. This study aims to determine the internalization of religious cultural values through religious activities at MTsN 3 Ponorogo, to determine the factors supporting and inhibiting the internalization of religious cultural values through religious activities at MTsN 3 Ponorogo, to determine the contribution of internalization of religious cultural values through religious activities. religion at MTsN 3 Ponorogo. This research uses a qualitative approach with the type of case study research. Data collection techniques using the method of observation, interviews, and documentation. Meanwhile, the data analysis technique uses the model analysis by Miles and Huberman with the following steps: data analysis, data reduction, data presentation, and drawing conclusions or verification. From the internalization of religious cultural values at MTsN 3 Ponorogo through religious activities, it can be seen that religious activities have been going well by paying attention to various aspects of students, the inhibiting factors are the culture of globalization, the influence of friends and the lack of religious education from parents. While the supporting factors are support from parents and all teachers at MTsN 3 Ponorogo, as well as the presence of students who are good in terms of worship can be a reflection for other students, and have an effect on increasing the discipline and awareness of students in worship, and social attitude and harmony in society.Key Word: Religious Cultural Values, Religious Activities, M.Ts. N 3 Ponorogo Abstrak Penelitian ini bertujuan untuk 1) mengetahui internalisasi nilai-nilai budaya religius melalui kegiatan keagamaan di MTsN 3 Ponorogo 2) untuk mengetahui faktor pendukung dan penghambat internalisasi nilai-nilai budaya religius melalui kegiatan keagamaan di MTsN 3 Ponorogo 3) untuk mengetahui kontribusi internalisasi nilai-nilai budaya religius melalui kegiatan keagamaan di MTsN 3 Ponorogo. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Teknik pengumpulan data dengan menggunakan metode observasi, wawancara, dan dokumentasi. Sedangkan teknik analisis data menggunakan analisis model Miles dan Huberman dengan langkah-langkah: analisis data, reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi. Hasil penelitian ini menunjukkan bahwa internalisasi nilai-nilai budaya religius di MTsN 3 Ponorogo melalui kegiatan keagamaan dapat berjalan dengan baik. Faktor penghambatnya adalah budaya globalisasi, pengaruh dari teman serta kurangnya pendidikan agama dari orang tua. Sedangkan faktor pendukungnya yaitu dukungan dari pihak orang tua dan semua guru di MTsN 3 Ponorogo, serta adanya peserta didik yang sudah baik dari segi ibadah dapat menjadi cerminan bagi peserta didik yang lainnya, serta berpengaruh dalam meningkatkan kedisiplinan dan kesadaran peserta didik dalam beribadah, serta sikap sosial dan kerukunan di masyarakat.Kata Kunci: Nilai Budaya Religius, Kegiatan Keagamaan, M.Ts. N 3 Ponorogo